Improving the Students’ Achievement in Writing Descriptive Text through Prepare, Organize, Write, Edit, Rewrite (POWER) Strategy - Daniel Panjaitan; Sumarsih (Universitas Negeri Medan, 2013)
This research concerned on Improving the Students’ Achievement in Writing Descriptive Texts through Prepare, Organize, Write, Edit, Rewrite (POWER) Strategy. In this research, the writer conducted classroom action research. Subject of this research were the second year students of SMK Negeri 1 Tanjung Pura Class XI AK consisted of 35 students. This research was conducted in two cycles. Each cycle was organized in four steps, namely Planning, Acting, Observing, and Reflecting. Cycle II was the improvement of Cycle I. There are two kinds of data collected during the research, qualitative and quantitative data. The instruments for the quantitative data was writing test while the qualitative data was gathered through Observation Sheet, Interview Sheet and Diary Notes. Findings showed that students’ score improved from Orientation Test to Test II. Based on the data analysis, Students’ mean in Orientation Test was 38.37, in Test I was 66.49, and Test II was 83.11. The conclusion is that the Prepare, Organize, Write, Edit, Rewrite (POWER) Strategy can improve the students’ achievement in writing descriptive text.